Teacher ratings of resilience and peer relationships of preschoolers whose fathers died unexpectedly. Issue 7 (8th August 2016) - Gülay Ogelman, Hülya; Gündoğan, Aysun; Erten Sarıkaya, Hatice; Erol, Ahmet
ABSTRACT: This study endeavors to compare resilience and peer relationships of children who lost their fathers in a major mining accident in Soma with those who did not. Teachers rated 51 preschoolers whose fathers died, and 53 preschoolers whose fathers were alive. On the negative side, bereaved children had lower resilience and higher exclusion; on the positive side, bereaved children had lower peer victimization and higher prosocial behavior. Death of fathers is associated with lower resilience and more exclusion among young children, but others treat them better as well.